2015
DOI: 10.1039/c5ra23730k
|View full text |Cite
|
Sign up to set email alerts
|

Effects of representative quantum dots on microorganisms and phytoplankton: a comparative study

Abstract: With the increasing application of semiconductor particles, especially metal-based quantum dots and carbon quantum dots (CQDs), these quantum dots will inevitably be released into the environment, and therefore their effects on biota should be assessed. Few studies on the effects of CQDs on microorganisms and phytoplankton have been performed. In this paper, we put forward more effective and convenient approaches to prepare three kinds of high-quality CQDs. Then we assessed their effects on Staphylococcus aure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
(27 reference statements)
0
12
0
Order By: Relevance
“…aeruginosa and C. pyrenoidosa. , For the first time, the present study investigated effects of CQDs on the growth of S. obliquus.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…aeruginosa and C. pyrenoidosa. , For the first time, the present study investigated effects of CQDs on the growth of S. obliquus.…”
Section: Resultsmentioning
confidence: 99%
“…CQDs treatments inhibited growth and induced oxidative damage in Chlorella pyrenoidosa . Similarly, treatments with 100 mg/L of CQDs significantly inhibited cell growth and decreased the chlorophyll-a content in Straphylococcus aureus and Microcystis aeruginosa . These results suggested that algae might be more sensitive to CQDs than fish.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…With the increasing application of semiconductor particles, especially metal-based QDs, these quantum dots will inevitably be released into the environment, and therefore their effects on biota should be assessed. Few studies on the effects of QDs on microorganisms and phytoplankton have been performed (Yan et al 2015a). A novel sensing system has been designed for the detection of m-phenylenediamine based on carbon QDs improved chemiluminescence in a luminol-potassium permanganate (KMnO 4 ) system.…”
Section: Introductionmentioning
confidence: 99%